Profile of Work Accidents in the Building and Public Works Sector BTP about 8 Companies in Conakry (Global Journal of Medical Research, 2023)
Introduction The building and civil engineering sector is a vast one encompassing a wide range of activities including the construction repair renovation and demolition of structures In the course of their activities workers are subjected to a variety of exposures including dusts and fumes asbestos uncomfortable postures and heavy loads Methodology This was a descriptive and analytical cross-sectional study lasting seven 07 months from November 25 2020 to June 27 2021 The city of Conakry served as the setting for the study The material consisted of workers on construction sites
Keywords: profile; work accident; building and public works; company